The building blocks of cellulose: the intrinsic conformational structures of cellobiose, its epimer, lactose, and their singly hydrated complexes. - Cocinero, E; Gamblin, D; Davis, B; Simons, J (2009)
A combination of vibrational spectroscopy conducted under molecular beam conditions and quantum chemical calculation has established the intrinsic three-dimensional structures of the cellulose disaccharide and, focusing on the critical beta1,4-linkage at the nonreducing end of the growing cellulose polymer, its C-4' epimer. Left to their own devices they both adopt a cis (anti-phi/syn-psi) glycosidic configuration, supported in the epimer by strong, cooperative inter-ring hydrogen bonding. In the cellulose disaccharide, however, where the OH-4'(Glc) group is equatorial, the cooperativity is reduced and the corresponding inter-ring hydrogen bonding is relatively weak. The cis conformational preference is still retained in their singly hydrated complexes. In the cellulose disaccharide insertion of the water molecule at the favored binding site between OH-4' and the neighboring hydroxyl group OH-6' promotes a structural reorganization to create a configuration that parallels that of its unhydrated epimer and greatly strengthens the inter-ring hydrogen bonding. In the C-4' epimer, the axial orientation of OH-4' blocks this binding site and the bound water molecule simply adds on at the end of the (OH-O)(n) chain, which has a negligible effect on the (already strong) inter-ring bonding. The implications of these results are discussed with respect to the structure and insolubility of native cellulose polymers.